Investigation of facilities and students’ readiness in supporting implementation of nodemcu-based bifocal modeling physics practicum - Sunardi Sunardi; Andi Suhandi; Deni Darmawan; Muslim Muslim (Momentum: Physics Education Journal, 2023)
This research was carried out to get overviews which deal with facilities and students’ readiness to support the implementation of NodeMCU-based bifocal modeling physics practicum. The location of this research was in a senior high school in Bandung District, Indonesia. The subjects of this research were physics teachers and students of that school enrolled in 2020/ 2021. This research was a case study, the data of which were collected through interviews, observation, and questionnaire. Interviews and observation were focused to gather information due to the school facilities supporting the implementation of NodeMCU-based bifocal modeling physics practicum. Questionnaire was used to reveal the readiness of students in accepting implementation of NodeMCU-based bifocal modeling physics practicum. Based on the data analysis, it was found that the school facilities meet technical specifications of NodeMCU, so the implementation of NodeMCU-based bifocal modeling physics practicum may be potentially supported by the school facilities; most students also own facilities (smartphones and laptops/ computers) which may be potentially utilized as output peripherals for displaying visualized physics phenomena and simulated physics data from a tool of NodeMCU-based bifocal modeling physics practicum; students are willing to accept the implementation of NodeMCU-based bifocal modeling physics practicum in physics learning, because it can improve the quality of physics learning, improve the motivation of students to learn physics, and help students to easily understand physics concepts.